Students’ Perceptions of Flood Mitigation at SMA Negeri 6 Anggrek District - Dewi Sartika Macmud; Fitryane Lihawa; Ramla Hartini Melo; Indrawan Indrawan (Universitas Negeri Gorontalo, 2026)
Floods are among the most frequent natural disasters in Indonesia and continue to disrupt educational activities, particularly in schools located in flood-prone areas. Strengthening students’ awareness and preparedness is therefore essential for enhancing school resilience and reducing disaster risk. This study aimed to examine students’ perceptions of flood disaster mitigation at SMA Negeri 6 Anggrek, North Gorontalo Regency, Indonesia, and to identify the relationship between their perceptions and preparedness levels. A quantitative descriptive approach was employed involving 191 students selected using proportional sampling. Data were collected through a Likert-scale questionnaire consisting of five indicators: understanding, attitude, preparedness, participation, and evaluation of school flood mitigation programs. Descriptive statistical analysis was conducted using mean score calculations for each indicator. The findings revealed that students demonstrated positive perceptions of flood disaster mitigation, reflected in good scores for understanding (3.82), attitude (3.74), participation (3.88), and evaluation of mitigation programs (3.70). However, preparedness obtained a lower mean score (2.95), indicating a moderate level of readiness. These findings highlight a gap between students’ positive perceptions and their practical preparedness for flood emergencies. The results suggest that knowledge and positive attitudes alone are insufficient to ensure disaster readiness without regular simulation activities, evacuation drills, and experiential disaster education. Strengthening school-based disaster preparedness programs is therefore essential to improve students’ capacity to respond effectively to flood hazards.